2013
DOI: 10.4236/aad.2013.23011
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospitalization and institutionalization in Medicaid patient populations with Alzheimer’s Disease

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…This is consistent with the fact that compared to non-Hispanic whites, African Americans are less likely to seek medical attention, and when they do, they present later in the disease course. A growing body of evidence suggests that African Americans are less likely than non-Hispanic whites to receive Alzheimer's treatment, such as ChEI therapy or memantine (Gilligan et al, 2012). Our current finding that African American females were associated with LOAD contributes to the existing literature on AD among African Americans.…”
Section: Discussionsupporting
confidence: 54%
“…This is consistent with the fact that compared to non-Hispanic whites, African Americans are less likely to seek medical attention, and when they do, they present later in the disease course. A growing body of evidence suggests that African Americans are less likely than non-Hispanic whites to receive Alzheimer's treatment, such as ChEI therapy or memantine (Gilligan et al, 2012). Our current finding that African American females were associated with LOAD contributes to the existing literature on AD among African Americans.…”
Section: Discussionsupporting
confidence: 54%
“…In a large, three-state study, Gilligan, Malone, Warholak, and Armstrong (2013a) found that, after controlling for demographics and pharmacotherapy exposure, African-American Medicaid beneficiaries with dementia were significantly more likely than their white counterparts to be hospitalized.…”
Section: Use Of Long-term Services and Supports And Other Health Servmentioning
confidence: 99%
“…Although research has suggested that individuals from ethnic minorities make use of many types of community support and educational resources when they are equally available, it has also suggested that disparities arise in access to quality long-term care. A meta-analysis by Cooper et al (2010) found that individuals of minority ethnicity were 40% less likely than Whites to enter a long-term care facility, and a similar finding was reported by Gilligan, Malone, Warholak, and Armstrong (2013b) in a Medicare-Medicaid sample from Florida, New Jersey, and New York.…”
Section: Social Services and Supportive Carementioning
confidence: 54%